The economic profiling, work performance and economic leakage of Rohingya refugees and Indonesian migrant workers in Klang Valley, Malaysia. - Mohd Safwan Ghazali (2021)
As of 2019, Malaysia has about 1.87 million lower-skilled workers. The number of migrant workers may double or triple the official number. The number of foreign workers has created three main problems: over-dependence on migrant workers, demanding migrant workers, and substantial economic leakage due to outward remittances. At the same time, there are about 180,000 refugees in Malaysia, especially the Rohingya from Myanmar. Both low-skilled workers and refugees will hamper Malaysia from becoming a developed country. Therefore, appropriate policies are needed to address the problems of over-dependence, demands, and economical drainage caused by the influx of lower-skilled migrant workers and refugees' permanent stay in Malaysia. One obvious solution is to replace demanding lower-skilled migrant workers with refugee workers. Therefore, it is imperative to empirically determine whether Malaysia can replace a portion of the lower-skilled migrant workers that Malaysia's economy depends on with a group of people whom Malaysia cannot dispense. The data set consists of quantitative data using 180 self-administered questionnaires from employed Rohingya refugees and Indonesian lower-skilled migrant workers and qualitative data using individual and cross-case analysis from 6 employers across the business sector. For this purpose, this study uses data triangulation to examine the two approaches. The analysis of the economic profiling reveals that Rohingyas refugees actively participate in the informal economy and working. Although Indonesian have better education, surprisingly, some Rohingya refugees have higher education qualifications against the common belief that refugees are illiterate. Many Rohingya respondents arrived with a nuclear family, signifying that the livelihood needs and return plans are different from other economic migrants. The findings also show that economic reason is the dominant push factor for Indonesian migrant workers looks for their futures outside their homes. Concerning psychological factors contributing to work performance, this study found that Rohingya workers' resilience attributes strongly cause individual work performance. Results also show that self-efficacy attributes are the main contributor to Indonesian migrant's work performance. Triangulated evidence indicates diverse opinions, with most employers optimistic that the government should replace lower-skilled migrant workers with refugee workers. Finally, this research also confirmed that Indonesian lower-skilled migrant workers remit money larger than Rohingya refugees due to differences in family structure and remittance motives. In the short run, UNHCR and the Malaysian government should provide some legal work status to Rohingya refugees to reduce the reliance on migrant workers. However, all stakeholders must work together to repatriate all refugees back to their home country or third countries in the long run.